Definition of HCV Reactivation [Letter] - Kaya A; Yıldız Kaya S (International Medical Case Reports Journal, 2021)
Abdurrahman Kaya,1 Sibel Yıldız Kaya2 1Department of Infectious Disease, Istanbul Training and Research Hospital, Istanbul, Turkey; 2Department of Infectious Disease, Sungurlu State Hospital, Istanbul, TurkeyCorrespondence: Abdurrahman KayaDepartment of Infectious Disease, Istanbul Training and Research Hospital, Istanbul, TurkeyTel +90 506 6113328Email dr.abdkaya@hotmail.com View the original paper by Dr Lensen and colleagues